Studies on the synthesis of the lasubine alkaloids. Issue 38 (20th September 2018) - Mohamed Aslam, Nur Filza bte; Simon, Oliver; Bates, Roderick W.
Abstract: Formal syntheses of lasubine II and subcosine II have been completed by the synthesis of epi -lasubine II. The synthesis involves diastereoselective allylation of a methoxy isoxazolidine and a tandem hydrogenation process leading stereoselectively to a trisubstituted piperidine. Graphical abstract: Image 1